Expression profiling the temperature-dependent amphibian response to infection by Batrachochytrium dendrobatidis. - Laia Ribas; Ming-Shi Li; Benjamin J Doddington; Jacques Robert; Judith A Seidel; J Simon Kroll; Lyle B Zimmerman; Nicholas C Grassly; Trenton W J Garner; Matthew C Fisher (PLoS ONE)
Amphibians are experiencing a panzootic of unprecedented proportions caused by the emergence of Batrachochytrium dendrobatidis (Bd). However, all species are not equally at risk of infection, and risk is further modified by environmental variables, specifically temperature. In order to understand how, and when, hosts mount a response to Bd we analysed infection dynamics and patterns of gene expression in the model amphibian species Silurana (Xenopus) tropicalis. Mathematical modelling of infection dynamics demonstrate the existence of a temperature-dependent protective response that is largely independent of the intrinsic growth-rate of Bd. Using temporal expression-profiling by microarrays and qRT-PCR, we characterise this response in the main amphibian lymphoid tissue, the spleen. We demonstrate that clearance of Bd at the host-optimal temperature is not clearly associated with an adaptive immune response, but rather is correlated with the induction of components of host innate immunity including the expression of genes that are associated with the production of the antimicrobial skin peptide preprocareulein (PPCP) as well as inflammatory responses. We find that adaptive immunity appears to be lacking at host-optimal temperatures. This suggests that either Bd does not stimulate, or suppresses, adaptive immunity, or that trade-offs exist between innate and adaptive limbs of the amphibian immune system. At cold temperatures, S. tropicalis loses the ability to mount a PPCP-based innate response, and instead manifests a more pronounced inflammatory reaction that is characterised by the production of proteases and higher pathogen burdens. This study demonstrates the temperature-dependency of the amphibian response to infection by Bd and indicates the influence that changing climates may exert on the ectothermic host response to pathogens.